A fluid monastic body: questions of re-bordering in nirthern Italy (twelfth-sixteenth centuries) - Alessandra Minotto; Anna Rapetti (Anuario de Estudios Medievales)
In this study, we aim to analyse some of the dynamics adopted by monastic communities in defining their environmental and jurisdictional space through boundaries. The wide geographical area under consideration and the long chronological span are appropriate dimensions on which to investigate phenomena that are not limited to the local level. The comparative analysis of sources concerning boundaries, produced by diverse and distant monastic communities, attests how the medieval monastic landscape was defined according to specific norms and customs that operated within the relationship between monks and their environmental resources, creating physical limits of inclusion and exclusion.